The use of the mother tongue in teaching French as a foreign language - Fatima Zohra SEHLAOUI (Langues & Cultures)
This study examines the problem of the use of the mother tongue in the teaching of foreign languages, in particular its influence on the learning of French as a foreign language, with a particular focus on oral interference among pupils in the fifth year of primary school. We analyse both the advantages and the limitations of integrating the mother tongue into the teaching and learning of French. The teacher faces multiple obstacles when trying to improve the understanding and acquisition of French through the mother tongue. This recourse influences both the way in which a foreign language is learned and the way in which it is taught, thus playing a mediating role in language learning situations.